Pengaruh Caatts dan Pengalaman Auditor terhadap Pendeteksian Fraud melalui Keahlian Forensik dan Audit Investigatif - Elsa Sayyidina Aulia; Indra Cahya Kusuma; Didi Didi (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
This study aims to evaluate the effect of CAATTs and auditor experience on fraud detection. To understand these two things, one model is used in this study, namely the CAATTs model and auditor experience after being mediated by forensic expertise and investigative audits and their significance on fraud detection. This research design is causality research or often known as explanatory research. The sampling technique is non-probability sampling with a saturated sample approach, which is distributed to auditors who work in various BPK RI units, including the Main Auditorate of State Finance I to VII and the Main Auditorate of Investigation. This research data comes from quantitative primary data obtained through online questionnaire distribution. The data analysis technique used PLS-SEM, utilizing SmartPLS 3.0 software. The results showed that CAATTs had no significant effect on fraud detection, while auditor experience had a significant effect on fraud detection. In addition, for the indirect effect, forensic expertise and investigative audit mediate the effect of CAATTs and auditor experience on fraud detection.